2020
DOI: 10.1521/soco.2020.38.supp.s187
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond the Relative Assessment of Implicit Biases: Navigating the Complexities of Absolute Measurement

Abstract: A relative assessment of implicit biases is limited because it produces a combined summary evaluation of two attitudinal beliefs while concealing the biases driving this evaluation. Similar limitations occur for relative explicit measures. Here, we will discuss the benefits and weaknesses of using relative versus absolute (individual/separate) assessments of implicit and explicit attitudes. The Implicit Association Test (IAT) will be the focal implicit measure discussed, and we will present a new perspective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 109 publications
1
7
0
Order By: Relevance
“…Because we had complete access to the raw IAT data (in contrast to the Project Implicit data set used in Studies 1a and 1b), we were also able to conduct several exploratory analyses to investigate the specific mental representations and processes that would be most impacted by these weight-related messages. While the traditional IAT D- score reflects the relative preference toward “thin” people over “fat” people, some have recently advocated considering each evaluative dimension separately (Blanton & Jaccard, 2017; Hicks et al, 2021; O’Shea et al, 2020; O’Shea & Wiers, 2020). With our current data, we could assess whether weight-related messages would result in changes in a person’s evaluative reactions toward “fat” people, “thin” people, or both.…”
Section: Study 2: Intraindividual Fluctuations In Implicit Bias: Rand...mentioning
confidence: 99%
“…Because we had complete access to the raw IAT data (in contrast to the Project Implicit data set used in Studies 1a and 1b), we were also able to conduct several exploratory analyses to investigate the specific mental representations and processes that would be most impacted by these weight-related messages. While the traditional IAT D- score reflects the relative preference toward “thin” people over “fat” people, some have recently advocated considering each evaluative dimension separately (Blanton & Jaccard, 2017; Hicks et al, 2021; O’Shea et al, 2020; O’Shea & Wiers, 2020). With our current data, we could assess whether weight-related messages would result in changes in a person’s evaluative reactions toward “fat” people, “thin” people, or both.…”
Section: Study 2: Intraindividual Fluctuations In Implicit Bias: Rand...mentioning
confidence: 99%
“…That is, SC-IAT performance revealed that participants had more positive than negative associations toward Black people, gay people, fat people, old people, Arab Muslims, and people with a disability, though interpreting a zero value in absolute indirect measures can be more difficult and ambiguous than in relative measures (O'Shea & Wiers, 2020).…”
Section: Descriptive Statistics and Mean-level Performancementioning
confidence: 99%
“…Researchers interested in exploring questions regarding individual differences in positive and negative implicit self-evaluations in healthy, nonclinical populations may benefit from modifying existing approaches or developing new measures for the primary purpose of assessing individual differences. For example, measures that do not rely primarily on difference scores, or accuracy-based or integrative measures which combine speed and accuracy into a composite score, may be appropriate (Draheim et al, 2019;Hedge et al, 2018;Miller & Ulrich, 2013;O'Shea & Wiers, 2020). Additionally, increasing the number of trials that each participant completes may increase the sensitivity of the EPT to assess implicit self-evaluations.…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 99%
“…Moreover, relative measures are often the most appropriate tool for addressing many research questions, given the importance of relative (vs. absolute) evaluations in judgment and behavior (Goffin & Olson, 2011; Olson et al, 2007). Nonetheless, because relative measures are not able to assess the coactivation of separate evaluations (O’Shea & Wiers, 2020), they are not the appropriate tool for assessing whether mental representations of the self automatically trigger both positive and negative evaluations (Kaplan, 1972; see Riketta & Ziegler, 2006 for a similar argument focused on relative measures of explicit self-esteem).…”
Section: Social Cognitive Conceptualizations Of the Personality Systemmentioning
confidence: 99%